2022
DOI: 10.1177/26318318221116042
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Sex and Pornography Addictions: A Primer

Abstract: Contrary to the earlier notion that addiction is predominantly a substance dependency, research now suggests that any source or experience capable of stimulating an individual has addictive potential. This has led to a paradigm shift in the psychiatric understanding of behavioural addictions. These can refer to a range of behaviors such as gambling, video gaming, and sexual practices. Hypersexual behavior and pornography addiction come to the fore when the behavior becomes intensive, out of the individual’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…However, a small minority of pornography viewers exhibit problematic internet pornography use (PIPU), with rates of 1-7% for women and 3-10% for men (3)(4)(5). Due to the similarities between PIPU and substance addiction in terms of occurrence and development mechanisms (6,7),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a small minority of pornography viewers exhibit problematic internet pornography use (PIPU), with rates of 1-7% for women and 3-10% for men (3)(4)(5). Due to the similarities between PIPU and substance addiction in terms of occurrence and development mechanisms (6,7),…”
Section: Introductionmentioning
confidence: 99%
“…However, a small minority of pornography viewers exhibit problematic internet pornography use (PIPU), with rates of 1–7% for women and 3–10% for men ( 3 5 ). Due to the similarities between PIPU and substance addiction in terms of occurrence and development mechanisms ( 6 , 7 ), PIPU is also referred to as online pornography addiction by many scholars and is typically defined as the inability to control excessive consumption of pornography despite its serious negative consequences ( 8 ). Research has found that internet pornography use is associated with many negative effects, such as physical health problems, emotional problems, and interpersonal relationship problems ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%